PUBLIC LAW AND PRIVATE LAW: TRANSFER OF LEGAL THEORIES - Ivan Padjen (Zbornik Radova Pravnog Fakulteta u Splitu, 2007)
If Ulpian’s dichotomy of law into public and private is not valid, it is irrelevant whether - and if so how - it has been transferred to Croatia. To that end the paper focuses on the International Encyclopedia of Comparative Law’s criticism of modern theories endorsing the dichotomy, finding that weaknesses of the criticism do not reinvigorate the dichotomy but reveal paradoxically onesidedness of the theories that endorse it. There are only a few indicators that the dichotomy has been transferred into Croatian legal culture. In the Croatian legal system The Law on Ownership and Other Real Rights (1991) Article 35 provides for that the Republic of Croatia and other juridical persons of public law as bearers of the right to ownership have the same rights in legal relations as private owners. In Croatian legal doctrine there are some short textbook reviews of the dichotomy, the most important being the division of law made by Berislav Perić on the basis o George Gurvitch’s theory. The only comprehensive contribution to the problem is Vladimir Vodinelic’s massive doctoral dissertation started at Split University and defended at Belgrade University in 1986. The paper offers a reconstruction of the dichotomy that starts from Aristotle’s analysis of justice. However, in contrast to Ernest Weinrib’s theory, which conceptualizes private law as being entirely distinct from public law, the reconstruction postulates that private law presupposes public law without the reverse being the case. The present author’s earlier view of the matter (that public law is created by statutes whereas private law is created by juridical acts) is amended by a distinction between three types of two-sided juridical acts, namely, contracts of exchange, contracts of legislation and of contracts of federation, the last one creating social law as a possible third area of law on the same footing as public law and private law. It is argued that the Croatian legal system still divides into the same three areas, as demonstrated by Berislav Perić. The fruitfulness of the trichotomy is demonstrated by the analysis of the Croatian law of civic associations. The trichotomy of law into public, private and social, is in accord with the European legal tradition. Moreover, the trichotomy may be considered exemplary for social democracy as analysed by Thomas Meyer.